O Parlamento do Mercosul em sua primeira fase: uma análise preliminar da transnacionalização da política no Cone Sul - George Gomes Coutinho (Ciências Sociais Unisinos)
The politics under the sign of globalization encounter in different locations of the world various forms of reaction, in central countries or in peripheral realities. This article discusses the Mercosur Parliament experience, situated in the Southern Cone, focusing these larger extension structural movements caused by the acceleration of the systemic-instrumental side of contemporary modernity. It is argued that this experience, in response to globalization, must be discussed related to the elements that distinguish the "negative modernity", which includes the permanent diffi culty of systemic-functional differentiation of its various subsystems. This fundamental point to describe the "negative modernity" is here mobilized as an explanatory factor for the diffi culties of establishing a transnational parliament in the peripheral capitalism.